The Influence of Fintech and Monetary Policy on Financial Stability in Indonesia - Seprianti, Viola Ditya; Syafii, M. (Fakultas Ekonomi dan Bisnis Universitas Ibn Khaldun Bogor, 2025)
The decline in financial system stability has negative consequences for the economy as a whole, such as declining economic growth, increasing political and social instability, increasing poverty rates, and so on. Therefore, research is needed to determine the appropriate policies to improve the stability of the Indonesian financial system. This study aims to examine the influence of fintech and monetary policy on the stability of the Indonesian financial system from 1982-2019. The method used is Vector Autoregression (VAR). The results of this study conclude that shocks that occur in gross domestic product (GDP), inflation (INF), exchange rates (KURS) and service features (FL) have a positive and significant impact on the stability of the Indonesian financial system. Meanwhile, shocks that occur in the amount of money in circulation (JUB), real interest rates (SBR), ease of use (KP) and information security risk (RKI) have a negative and significant impact on the stability of the Indonesian financial system.